Boosting Organic–Metal Oxide Heterojunction via Conjugated Small Molecules for Efficient and Stable Nonfullerene Polymer Solar Cells. Issue 34 (30th July 2019) - Liu, Haoran; Liu, Zhi‐Xi; Wang, Shuxu; Huang, Jiang; Ju, Huanxin; Chen, Qi; Yu, Junsheng; Chen, Hongzheng; Li, Chang‐Zhi
Abstract: Charge events across organic–metal oxide heterointerfaces routinely occur in organic electronics, yet strongly influence their overall performance and stability. They become even more complicated and challenging for the heterojunction conditions in polymer solar cells (PSCs), especially when nonfullerene acceptors with varied energetics are employed. In this work, an effective interfacial strategy that utilizes novel small molecule self‐assembled monolayers (SAMs) is developed to improve the electronic and electric, as well as chemical properties of organic–zinc oxide (ZnO) interfaces for nonfullerene PSCs. It is revealed that the tailored SAMs with well‐controlled energy levels and molecular dipoles can effectively optimize the energetic barrier and work function (WF) of heterointerface for optimal electron extraction. In addition, the introduction of SAMs atop of ZnO facilitates not only acceptor segregation near the n‐contact interface, but also passivation of the photocatalytic activities for ZnO, to improve overall performance and photo stability of the derived nonfullerene PSCs. Overall, the methodology and structure–property relationship revealed herein would be beneficial for a wide range of hybrid electronics. Abstract : The introduction of funtional molecular self‐assembled monolayers (SAMs) atop of zinc oxide (ZnO) effectively optimizes the energetic and heterojunction properties of the organic–metal oxide interface to improve the performance and photostability of nonfullerene polymer solar cells.